Assessment of Financial Performance of A Traditional Market Rehabilitation in Surabaya - ICCER Sipil ITS (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2026)
The traditional market in Surabaya constitutes a critical hub of commercial activity for the local community. However, over time, the physical condition and infrastructure of most traditional market area have markedly declined. Numerous buildings are structurally outdated and fail to comply with current safety and comfort standards. Consequently, the revitalization of the traditional market has become an urgent imperative to enhance market quality and strengthen the local economy. The revitalisation of the traditional market needs many aspects to be decided, including design, construction, and finan-cial aspects during its life cycle. This research studies financial feasibility of the one of traditional market in Surabaya using two alternatives. The finan-cial performance compares cost and benefit estimated over 30 years as its life cycle using parameters of Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Payback Period (PP). The study generates negative NPV and BCR < 1 both two alternatives. It indicates that the revitalization is not fea-sible. The project will be feasible if it estimates over 36 years using the sec-ond alternatives. The analysis generates IDR 126.057.465,65 of NPV and BCR value > 1.